(untitled) (Journal of Engineering, 2024)
This study aims to find the best conditions of resistance spot welding in commercial Aluminium AA1050 to obtain the maximum tensile shear strength of the joint using a low-power supply welding machine. The chosen parameters for this study were welding current, welding time, and electrode force using a 90 kVA welding machine. The investigation used the DoE method with Taguchi’s technique to reduce the number of experiments where two sheet thicknesses (1 mm and 2 mm) were used in this work. The software program Minitab 18 analyzed the results using the main effects plots and the interaction plots to identify the most significant parameters and their effect on the joint strength. The best conditions for maximum tensile shear force were 14.85 kA welding current and 0.79 kN electrode force for both thicknesses and two cycles and 12 cycles welding time for 1 mm and 2 mm sheet thickness, respectively. The maximum tensile strength obtained was 250 N and 225 N for 1mm and 2mm sheet thickness, respectively. A mathematical equation was developed to predict the shear force with 19.9 % and 17.9 % error for 1 mm and 2 mm thicknesses, respectively. The best conditions were applied in ANSYS 2022R1 multi-physics to obtain the temperature distribution with time history, where the result shows the nugget size according to the molten temperature. The percentage of discrepancy between actual and numerical nugget size was 8 %.